1974
DOI: 10.1136/gut.15.5.360
|View full text |Cite
|
Sign up to set email alerts
|

Fat-reduced diet in the treatment of hyperoxaluria in patients with ileopathy

Abstract: SUMMARY Thirteen patients with ileopathy were studied under metabolic ward conditions, first on a 100-g fat diet and later on a 40-g fat diet. Ten of the patients were studied after three to 27 months on a fat-reduced diet. Ten of the patients had a high urinary oxalate excretion on the high-fat diet compared with a control group. The patients with a faecal fat output of more than 15 g a day showed a reduction in oxalate excretion when the fat intake was decreased and in the follow-up study the oxalate excreti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

1976
1976
2010
2010

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(35 citation statements)
references
References 12 publications
0
35
0
Order By: Relevance
“…A small reduction in urinary oxalate can significantly reduce the risk of forming calcium oxalate stones (see earlier), therefore, avoiding oxalate-rich foods (spinach, rhubarb, beetroot, soya beans and tofu, nuts, peanut butter, okra, yams, sesame seeds, tahini and chocolate) is justified, even if the contribution of dietary oxalate to urinary oxalate excretion is limited [46]. A reduction in dietary fat intake can decrease urinary oxalate excretion: in 13 patients with disease of the ileum (mainly due to Crohn’s disease) who switched from a 100- to a 40-gram fat diet, oxalate excretion decreased slowly, but significantly, up to 50%, if faecal fat excretion fell to <15 g/day [47]. In patients with significant hypercalciuria and a high calcium intake (particularly if derived from dairy produce, the more absorbable form), some reduction in dietary calcium with oxalate may be justified.…”
Section: Medical Managementmentioning
confidence: 99%
“…A small reduction in urinary oxalate can significantly reduce the risk of forming calcium oxalate stones (see earlier), therefore, avoiding oxalate-rich foods (spinach, rhubarb, beetroot, soya beans and tofu, nuts, peanut butter, okra, yams, sesame seeds, tahini and chocolate) is justified, even if the contribution of dietary oxalate to urinary oxalate excretion is limited [46]. A reduction in dietary fat intake can decrease urinary oxalate excretion: in 13 patients with disease of the ileum (mainly due to Crohn’s disease) who switched from a 100- to a 40-gram fat diet, oxalate excretion decreased slowly, but significantly, up to 50%, if faecal fat excretion fell to <15 g/day [47]. In patients with significant hypercalciuria and a high calcium intake (particularly if derived from dairy produce, the more absorbable form), some reduction in dietary calcium with oxalate may be justified.…”
Section: Medical Managementmentioning
confidence: 99%
“…Until recently most investigators had concluded that oxalate was absorbed by a passive, noncarrier-mediated pathway and that increased absorption resulted from increased passive permeability and/or increased solubility of oxalate (2)(3)(4)(7)(8)(9)(10)(11)(12)(13)(14). Hatch et al (15), SITS),' which suggests an anion exchange process on the brush border.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms promoting increased oxalate absorption are thought to be as follows: solubility [4,10]; permeability [11], and reduction of oxalate degradation by intestinal bacteria [12] (fig. 3).…”
Section: Discussionmentioning
confidence: 99%